Seismic damage analysis of Yematan Bridge under near-fault earthquakes. (July 2022) - Zu, Lin; Huang, Yong; Li, Wenshan; Zhang, Haoyu; Cai, Liwen
Abstract: On May 22, 2021, a magnitude 7.4 (Ms) earthquake, the largest earthquake in mainland China since the Wenchuan magnitude 8.0 (Ms) earthquake, occurred in Maduo County, Qinghai Province, China. The Maduo earthquake caused significant damage to the Yematan Bridge near the fault and epicenter, which resulted in excessive girders movement and the widespread failure of high damping bearings. The seismic performance of the Yematan Bridge was studied by finite, which simulated the mechanical behavior of the shear key and high damping bearings. To better restore the seismic damage situation, nonlinear analysis is carried out by using two constitutive models of high damping rubber bearings with and without damage. The ground motion input contains near-fault features concluded directivity effect and fling step, and genetic algorithm is used to find the optimal ground motion amplitude for seismic response analysis. The analysis showed that one of the essential reasons for the severe damage to the bridge is that the bridge axis is close to the predominant seismic angle, and the bearing was damaged by the directivity effect. The calculation results obtained by considering the bearing failure constitutive model are closer to the field investigation of earthquake damage. Finally, corresponding seismic measures and suggestions are proposed according to the seismic damage situation and mechanism of the bridge.